2014
DOI: 10.1186/1471-2334-14-197
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary immune responses to 2009 pandemic influenza A (H1N1) virus in mice

Abstract: BackgroundWell-characterized mice models will afford a cheaper, easy-handling opportunity for a more comprehensive understanding of 2009 influenza A (H1N1) virus’s pathogenesis potential. We aimed to provide a robust description of pulmonary immune responses in the mice infected by the virus.MethodsBALB/c mice were inoculated intranasally with A/Beijing/501/2009(H1N1) (BJ501) and A/PR/8/34(H1N1) (PR8) viruses and compared for survival rate, viral replication, and kinetics of pulmonary immune responses.ResultsB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…We found that TNF- α and IL-1 β levels were below the detection limit for most of the days after infection (data not shown) for both high dose (1000 TCID50) groups treated with oseltamivir either prophylactic or therapeutic regimen. The results are in accordance with the study by [ 11 ], where 5 × 10 5 plaque forming units of PR8 virus infection only transiently increased the TNF- α level at 2 days after infection. Also it has been shown that viral strain differences (BJx109 and PR8 virus) in the local inflammatory response in stimulating the release of type I IFNs [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that TNF- α and IL-1 β levels were below the detection limit for most of the days after infection (data not shown) for both high dose (1000 TCID50) groups treated with oseltamivir either prophylactic or therapeutic regimen. The results are in accordance with the study by [ 11 ], where 5 × 10 5 plaque forming units of PR8 virus infection only transiently increased the TNF- α level at 2 days after infection. Also it has been shown that viral strain differences (BJx109 and PR8 virus) in the local inflammatory response in stimulating the release of type I IFNs [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Inflammation due to viral diseases is rapid and nonspecific host defense mechanism against infection is intricately regulated by a network of mediators which include inflammatory cytokines. The extent of lung injury in severe influenza infections may be in part due to overly exuberant or dysregulated innate inflammatory responses [ 11 ]. Several studies have examined correlation of flu disease parameters such as viral shedding and symptom scores with levels of IL-6 [ 12 , 13 ], which was recently reported as a potential biomarker of severity in pandemic influenza infections [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, animal models continue to show promise in cultivating an understanding of how influenza affects human hosts. Mouse models continue to be the most popular choice for in vivo influenza studies, as mice are inexpensive and reagents are easily obtainable [56]. Swine and primates represent the best non-human animal models for understanding influenza.…”
Section: Discussionmentioning
confidence: 99%
“…The expressions of IL-4 [55] and IL-10 [56] are related to TNF-a level. IL-4, a Th2 signature cytokine, is produced by TC2 cells [57] and is proved to be produced by IL-4+ secreting cells in the late recovery phase [53]. IL-10, considered as an important anti-inflammatory cytokine, acts as a negative regulator of the response of both innate and adaptive immune cells and is produced in the infected lungs at high level by antiviral CD8+ and CD4+ effector T-cells during acute influenza infection [58].…”
Section: Number Of Animals With Infection Signs/total Number Of Animamentioning
confidence: 99%